Ответ:
Пошаговое объяснение:
14)
2х -(3х - 2) * (-3) = 2 * 2х - 2
2х + 3(3х -2) = 4х - 2
2х + 9х - 6 = 4х - 2
11х - 4х = -2 + 6
7х = 4
х = 4/7
15)
3 - 2(4 - 2х) - (6 - 3х) * (-2) = 8 * 3(2 - 2х)
3 - 8 + 4х + 12 - 6х = 48 - 48х
-2х + 48х = 48 - 7
46х = 41
х = 41/46
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
14)
2х -(3х - 2) * (-3) = 2 * 2х - 2
2х + 3(3х -2) = 4х - 2
2х + 9х - 6 = 4х - 2
11х - 4х = -2 + 6
7х = 4
х = 4/7
15)
3 - 2(4 - 2х) - (6 - 3х) * (-2) = 8 * 3(2 - 2х)
3 - 8 + 4х + 12 - 6х = 48 - 48х
-2х + 48х = 48 - 7
46х = 41
х = 41/46